Chronic Crohn's disease: diagnosis and management at the present times - V.A. Klimenko; O.V. Piontkovska; O.S. Lupaltseva; T.O. Khalturina; O.M. Savvo; N.I. Timokhina; G.M. Soboleva (Zaslavsky O.Yu., 2018)
The article deals with the data on the prevalence, diagnosis, treatment, prevention of bacterial and fungal infections in children with chronic granulomatous disease.